RETRACTED: Assessment of the frame strength of a passenger trolley model KVZ-TsNII in the Femap software package - Martynenko L.V.; Tsvik L.B. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001